(untitled) (Research, Society and Development, 2021)
Xylose is the second most abundant monosaccharide in nature. Xylose monomers are part of the structure of hemicellulose, which shows amorphous structure and is easily degraded by acid hydrolysis. Xylose is widely studied for xylitol and biofuels production; however, it is still little explored for the production of biosurfactants, which are active surface molecules with emulsifying properties, are biodegradable and are non-toxic to the environment. Bacteria, fungi and yeasts are extensively studied for the production of biosurfactants from different carbohydrates, oils and hydrocarbons, but there are few reports in the literature about the production of biosurfactants from hemicellulosic hydrolysates rich in xylose. Some studies show that bacteria and yeasts generally produce glycolipids from hemicellulosic hydrolysates. Due to the different properties of glycolipids, they can be used in different areas of industry, as they can be applied as bioremediators, bioinsecticides and antimicrobials.